Red Tit and Brown Tit - Barlow, Alex.; Jose, Ellen (South Melbourne, Vic. : Macmillan Company of Australia, 1991)
A story from the Pitta-Pitta people who own the land around Boulia, a town in Western Queensland. It tells of how red tit came to have a red head and breast and brown tit a flattened head and beak.
"An expanded version of the Pitta-Pitta story originally recorded by W.E. Roth in the first volume of his The Queensland Aborigines published in 1897" --Inside front cover.
For children.
Keywords: Readers (Primary); Readers -- Aboriginal Australians -- Folklore; Birds -- Australia -- Folklore; Readers -- Birds -- Australia; Aboriginal Australians -- Ethnozoology -- Queensland -- Juvenile literature; Literature and stories - Juvenile; Stories and motifs - Birds; Pitta Pitta / Bittha Bittha people (G6) (Qld SF54-10); Boulia (Qld Far West SF54-10)